Observed and calculated properties of mid-level, mixed-phase clouds - Seaman, Curtis J., author; Vonder Haar, Thomas H., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 2003)
The University of Wyoming King Air research aircraft was flown into five mid-level clouds that formed over the western Great Plains during the Ninth Complex Layered Cloud Experiment (CLEX-9). Four of the clouds were mixed-phase. This study presents the direct observations made of these clouds as well as the cloud properties that were derived from these observations. In particular, profiles of temperature, water vapor mixing ratio, liquid water content (LWC) and ice water content (IWC) are shown. These profiles were used to calculate profiles of latent heating rate, and long- and shortwave radiative heating rate. In-cloud temperatures were observed between +2 °C and -25 °C. Maximum horizontally averaged LWC and IWC values were between 0.04 - 0.28 g m-3 and 0 - 0.16 g m-3 respectively. Cloud depths ranged from 248 m to 3106 m, with cloud bases between 2.9 and 5.6 km above mean sea level. Direct observations of ice particles made through the use of 2D-C and 2D-P optical imaging probes were analyzed using the methods of Heymsfield et al. (2002) to account for departures from sphericity, which reduces the observed ice water content by as much as 95%. These methods were also used to fit the observed ice particle size distribution into a modified gamma distribution equation, from which the ice particle effective radii were determined. Knowledge of the ice particle effective radii, plus observations of the liquid droplet effective radii made by a Forward Scattering Spectrometer Probe, were used with the profiles of LWC and IWC to calculate liquid and ice water paths and optical depths of these clouds. Ice particle size distributions and profiles of IWC show evidence of growth by the Wegener-Bergeron-Findeisen mechanism and aggregation. This data was input into a simple model to calculate the relative importance of subsidence, radiation, entrainment and precipitation in affecting cloud lifetimes. Results of this model show that subsidence and precipitation are the most important processes. It is also shown that the passage of potential vorticity anomalies may be intricately linked to the lifetimes of isolated, non-frontal and non-orographic mid-level clouds. A selection of previous studies was examined in light of these results to develop a consistent picture of the lives of midlevel clouds. The results of this study are shown to be similar to the results of previous studies of mid-level clouds, particularly those that took place over the continental United States.
Keywords: Cloud physics; Clouds -- Observations